Exploring Luxury Travel from the Perspective of Ancillary Services Supplier: High-End Vehicles and Limousine Service. - Norliza Aminudin; Anis Sofia Kamal; Salamiah A. Jamal; Faiz Izwan Anuar (International Journal of Supply Chain Management, 2018)
The purpose of the study is to explore oneof the ancillary services in tourism namely high-endvehicles and limousine service and identify its currentsupply, benefits, potential and challenges from thesupply perspective. As the study on the topic isrelatively new and intended to understand theexperience of the service providers in Malaysiasetting, qualitative study using case study approachwas adopted as the study methodology. The scope ofthe study covers the perspective of the supplier orservice providers of high-end vehicles and limousineservice in Malaysia. From the findings, it is agreedthat the provision of the service could positivelyenhance destination image and spurs tourism growththrough top notch delivery service. However, industryoverview and challenges revealed that insufficientsupply of vehicles, illegal use of privately-ownedvehicles for the service and shrinkage in economicgrowth, high cost of business operation, lack of accessto information and assistance as well as issue ofsustainability may hinder the potential to developgood destination image and stimulate tourismspending. To overcome these challenges, possiblerecommendations that can be suggested arefacilitating the industry through government support,embracing innovative business model to sustain andstimulating larger demand through vibrantattractions as pull factor. In conclusion, the high-endvehicles and limousine service industry has to be clearwith its actual target segmentation, embraceinnovation to build market capabilities andstrengthen its position and capabilities throughbusiness association. Future studies may include study from the demand perspective and comparisonstudy between popular high-yield tourists'destinations.INKeywords Ancillary service, Luxury travel, High-yieldtourist, High-end vehicles service, Supply perspective